SEPARATION AND ASSAY OF LYSINS AND LYSIN-INHIBITOR COMPLEXES IN BLOOD AND TISSUES - Ponder, Eric (The Rockefeller University Press, 1952)
1. A process of extraction and assay, which combines the features of several existing methods, is described for the lytic materials which can be obtained from blood, plasma, serum, and tissues. At least two alcohol-soluble substances, one ether-soluble ("soap-like") and the other insoluble in ether in the cold ("lysolecithin-like"), can be obtained from preincubated blood, plasma, or serum. The hemolytic activity (or concentration) of the soap-like lysin obtained from blood is greater than that of the lysolecithin-like substance, but for plasma and serum the reverse is true, i.e. the red cells are involved in the production of the soap-like lysin, and probably supply some of it when acted upon by enzymes contained in plasma and serum. Preincubation of the blood or plasma increases the yield of lysin two- or threefold, and small quantities of both soap-like and lysolecithin-like lysins can be obtained from unpreincubated blood or plasma. 2. The soap-like lysins obtained from preincubated mouse liver are some 5 to 15 times as active as, or occur in some 5 to 15 times the concentration of, those obtained from blood or plasma. The lysolecithin-like lysins of preincubated liver are about twice as active as, or occur in about twice as great concentration of, those obtained from blood. Because of the shape of the time-dilution curve for these lysins, the relations between their activities, or concentrations, are often quite different from those which one would anticipate if one were to consider only the times required for the production of hemolysis. 3. Paper chromatography can be used to separate the soap-like and the lysolecithin-like lysins obtainable from small quantities of preincubated mouse liver homogenates or preincubated mouse blood. The presence of lysins is detected by their effect on the red cells of a suspension as it wets the paper. Various technical procedures for separating lytic components and for demonstrating that they move on the paper along with protein components are described. 4. Paper strip electrophoresis can be used to show that the supernatant fluid of a preincubated mouse liver homogenate contains at least two protein components and at least two lytic components, not very closely associated in their electrophoretic behavior. 5. Observations on the physical nature of the alcohol- and ether-soluble lysin point to its having a soap-like character. Its activity, as well as that of the lysolecithin-like lysin, is inhibited by cholesterol, by lecithin, and by various fractions of serum. Some of these effects have been studied quantitatively. The most inhibitory of the protein fractions are those which contain lipoproteins; i.e., II + III and IV + V.